Hypoxia-Mimetic CoCl2 Agent Enhances Pro-Angiogenic Activities in Ovine Amniotic Epithelial Cells-Derived Conditioned Medium - Miriam Di Mattia; Annunziata Mauro; Simona Delle Monache; Fanny Pulcini; Valentina Russo; Paolo Berardinelli; Maria Rita Citeroni; Maura Turriani; Alessia Peserico; Barbara Barboni (Cells, 2022)
Amniotic epithelial stem cells (AECs) are largely studied for their pro-regenerative properties. However, it remains undetermined if low oxygen (O2) levels that AECs experience in vivo can be of value in maintaining their biological properties after isolation. To this aim, the present study has been designed to evaluate the effects of a hypoxia-mimetic agent, cobalt chloride (CoCl2), on AECs’ stemness and angiogenic activities. First, a CoCl2 dose-effect was performed to select the concentration able to induce hypoxia, through HIF-1α stabilization, without promoting any cytotoxicity effect assessed through the analysis of cell vitality, proliferation, and apoptotic-related events. Then, the identified CoCl2 dose was evaluated on the expression and angiogenic properties of AECs’ stemness markers (OCT-4, NANOG, SOX-2) by analysing VEGF expression, angiogenic chemokines’ profiles, and AEC-derived conditioned media activity through an in vitro angiogenic xeno-assay. Results demonstrated that AECs are sensitive to the cytotoxicity effects of CoCl2. The unique concentration leading to HIF-1α stabilization and nuclear translocation was 10 µM, preserving cell viability and proliferation up to 48 h. CoCl2 exposure did not modulate stemness markers in AECs while progressively decreasing VEGF expression. On the contrary, CoCl2 treatment promoted a significant short-term release of angiogenic chemokines in culture media (CM). The enrichment in bio-active factors was confirmed by the ability of CoCl2-derived CM to induce HUVEC growth and the cells’ organization in tubule-like structures. These findings demonstrate that an appropriate dose of CoCl2 can be adopted as a hypoxia-mimetic agent in AECs. The short-term, chemical-induced hypoxic condition can be targeted to enhance AECs’ pro-angiogenic properties by providing a novel approach for stem cell-free therapy protocols.